Effect of Main Engine Placement and Propeller Shaft Inclination on Ship Performance - Santoso, Agoes; Arief, Irfan Syarief; Masro’i, Ngizuddin; Semin, (International Journal of Marine Engineering Innovation and Research, 2025)
Placement of the ship propulsion system components might also affect the value of the ship's resistance and thrust. Included in the placement of the ship's propulsion system components are the placement of the main engine and propeller shaft inclination. Changes in the placement of the main engine will affect the location of the center of gravity of the ship which affects the trim and the amount of resistance of the ship. While propeller shaft inclination will affect the direction of thrust produced by the propeller. In this research, an analysis of how big the effect of the placement of the main engine and the propeller shaft inclination on various angles for the 60 GT fishing vessel on the ship's performance by using simulation. Simulations were performed with Numeca Fine Marine software using the Actuator Disk Propeller method. Propeller shaft inclination variations are 1°, 2°, 3°, and 4°. At each propeller shaft inclination, there are two variations of the placement of the main engine at a distance of 4m-6.5m from the AP and 5.5m-8m from the AP. Based on the results of the simulation that has been done, the greater the angle of the propeller shaft inclination, the more resistance value will be even smaller, and the thrust produced is also smaller. When the main engine is shifted towards FP, the resistance value will be greater, and the thrust generated is also greater. The most optimal conditions are on the rake of the propeller shaft 4° and the main engine position 4m-6.5m from the AP, the total resistance value of the ship = 9648.97 N and the thrust = 16520.66, torque = 1867.46, KT = 0.1569, KQ = 0.0177, J = 0.2827 and propulsion efficiency = 0.3991. This configuration was chosen because to make the ship move at the same speed, the configuration requires less power.